Menjaga Keutuhan Pesan Agama : Urgensi Konteks dalam Memahami Teks Keagamaan - M. Samsul Ma'arif; Diah Dwi Ikranegara (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2025)
Abstract : The problem of understanding is crucial because misunderstanding can have fatal consequences. This awareness of understanding needs to be instilled in understanding various symbols and signs, including texts and symbols related to religion. This research aims to address the effectiveness of understanding religious language, and how generations living in different times and places are able to grasp the ideas of religious texts correctly and comprehensively from previous generations. This research is a literature review using a qualitative-descriptive approach to analyze various relevant books and scientific journal articles. The study concludes that interaction with religious texts is not merely about reading and understanding the text but also requires a comprehensive, contextual understanding of its context and message. Ignoring the context of space and time is very dangerous, as it will present an incomplete, unequal, and even problematic image of religion.Keywords: Religious Messages, Religious Texts, Urgency of Context.Abstrak: Problem memahami merupakan hal penting karena salah memahami berakibat fatal. Kesadaran memahami ini perlu dibawa untuk memahami berbagai simbol dan tanda, termasuk teks dan simbol yang terkait dengan agama. Penelitian ini bertujuan untuk menjawab efektifitas memahami bahasa agama, bagaimana generasi yang hidup di zaman dan tempat yang berbeda mampu menangkap gagasan teks agama secara benar dan utuh dari generasi sebelumnya. Penelitian ini merupakan studi pustaka dengan pendekatan kualitatif-deskriptif untuk melakukan analisis berbagai literatur buku-buku yang relevan dan berbagai artikel jurnal ilmiah yang relevan. Sebagai hasil kajian, interaksi dengan teks keagamaan tidaklah cukup dengan kecakapan membaca dan mengetahui teks saja melainkan harus dengan memahami konteks serta pesannya secara komprehensif kontekstualis. Terabaikannya konteks ruang dan waktu sangat berbahaya, karena justru akan menampilkan wajah agama yang tidak utuh, timpang bahkan bermasalah.Kata kunci: Pesan Agama, Teks Keagamaan, Urgensi Konteks.